EFFECT OF THE DOWNWASH FLOW FIELD OF A SINGLE-ROTOR UAV ON DROPLET VELOCITY IN SUGARCANE PLANT PROTECTION - Zhang,Ping (2021)
ABSTRACT Protecting against the main sugarcane diseases and insect pests requires good control at the base of the plant; therefore, higher droplet penetration is required during plant protection. The objectives of this research were to explore the movement mechanism of droplets in a sugarcane protection operation using a single-rotor unmanned aerial vehicle (UAV) and establish the connection between the UAV downwash flow field and droplet penetration. By considering the downwash flow field of a single-rotor UAV in layers, a theoretical model of the vertical velocities of droplets was established, and verification experiments were carried out in a sugarcane field. The results showed that the velocity of the UAV downwash flow was the main factor affecting the final vertical velocity of the droplets, the final vertical velocity of a droplet was positively correlated with the droplet diameter, and the initial droplet velocity had no significant effect on the final droplet velocity. In the transportation of droplets, the droplet velocity quickly approached the velocity of the airflow, and the smaller the droplet diameter was, the higher the acceleration. These research results can provide guidance for the theoretical study of droplet deposition effects in sugarcane protection operations using single-rotor UAVs.